The Sage handbook of research management - Dingwall, Robert; McDonnell, Mary Byrne (Los Angeles ; London : Sage reference, 2015)
The Handbook of Research Management is a unique tool for the newly promoted research leader. Larger-scale projects are becoming more common throughout the social sciences and humanities, housed in centres, institutes and programmes. Talented researchers find themselves faced with new challenges to act as managers and leaders rather than as individual scholars. They are responsible for the careers and professional development of others, and for managing interactions with university administrations and external stakeholders. Although many scientific and technological disciplines have long been organized in this way, few resources have been created to help new leaders understand their roles and responsibilities and to reflect on their practice. This Handbook has been created by the combined experience of a leading social scientist and a chief executive of a major international research development institution and funder. The editors have recruited a truly global team of contributors to write about the challenges they have encountered in the course of their careers, and to provoke readers to think about how they might respond within their own contexts. This book will be a standard work of reference for new research leaders, in any discipline or country, looking for help and inspiration. The editorial commentaries extend its potential use in support of training events or workshops where groups of new leaders can come together and explore the issues that are confronting them.--
/>Using Research Process to Improve Research Practice -- Jacqueline Williams Kaye Moving on? -- Barbara Czarniawska
Includes bibliographical references and index.
Rasal
Keywords: Research -- Management -- Handbooks, manuals, etc; Research -- Management; Sozialwissenschaften; Empirische Sozialforschung; Forschungsprojekt; Projektmanagement; Forskningsorganisation; General